Research Advances on 2D Mxenes for Photovoltaic Applications - Akanbi, Opeyemi; Abass, Gbemi; Ige, Akinsanmi; Nyatse, Daniel; Oyeshola, Hakeem; Abba, Haruna; Felix, Olusegun; Oni, Kehinde; Ayotunde, Alabi; Ajao, Joshua; Akinade, Hammed; Oladejo, Abiodun; et al. (Journal of Advanced Mechanical Engineering Applications, 2023)
MXene, a two-dimensional nanomaterial, has an impressive range of properties that make it a perfect choice for a variety of applications, including energy systems, high-tech sensors, optics, medical devices, and electromagnetic interference shielding. Its high carrier mobility, metallic electrical conductivity, superior transparency, excellent mechanical characteristics, and tunable work function have drawn much attention. This review examines the utilization of MXene in solar technology, highlighting its potential as an electrode, charge carrier, and additive in quantum dot-sensitized, perovskite, silicon wafer-based, and organic solar cells. Additionally, a summary table is provided that briefly outlines the different methods of synthesizing MXene and their respective etching chemicals and precursors. This review’s latter part looks at the challenges associated with MXene and offers potential solutions and prospects.